Revealing the Lived Experiences of Alternative Learning System (ALS) Volunteer-Teacher in the New Normal: An Inquiry - Verna Jeane Q. Alviso; Jeanilyn E. Tacadena (Journal of Learning and Educational Policy, 2023)
This research study aimed to explore the lived experiences of volunteer teachers in Alternative Learning System (ALS) in the new normal modality of teaching. A qualitative research design was employed, specifically utilizing phenomenological approach. The study focused on the experiences, coping mechanisms, and the insights drawn from the experiences of the 14 ALS volunteer-teachers of the Division of Davao de Oro, seven (7) of whom undergone in-depth interviews, while the remaining seven (7) underwent focus group discussion. Data were analyzed using thematic analysis. The findings revealed major themes on the experiences of the ALS volunteer-teachers in the new normal: extend extra effort, mixed emotion and limited resources. On the other hand, the participants cope with the challenges through: Tenacity to help and teach, Inspiration from Students’ Determination and Collaborating with others. The findings present substantial information for policymakers to review and provide substantial support to the volunteer-teachers who traversed and provided learning resources to the learners despite the pandemic. To be able to capture a more generalizable findings, future study utilizing a bigger group and scope is recommended.